Global initiative for meticillin-resistant Staphylococcus aureus pneumonia (GLIMP): an international, observational cohort study. Issue 12 (December 2016) - Aliberti, Stefano; Reyes, Luis F; Faverio, Paola; Sotgiu, Giovanni; Dore, Simone; Rodriguez, Alejandro H; Soni, Nilam J; Restrepo, Marcos I; ,
Summary: Background: Antibiotic resistance is a major global health problem and pathogens such as meticillin-resistant Staphylococcus aureus (MRSA) have become of particular concern in the management of lower respiratory tract infections. However, few data are available on the worldwide prevalence and risk factors for MRSA pneumonia. We aimed to determine the point prevalence of MRSA pneumonia and identify specific MRSA risk factors in community-dwelling patients hospitalised with pneumonia. Methods: We did an international, multicentre study of community-dwelling, adult patients admitted to hospital with pneumonia who had microbiological tests taken within 24 h of presentation. We recruited investigators from 222 hospitals in 54 countries to gather point-prevalence data for all patients admitted with these characteristics during 4 days randomly selected during the months of March, April, May, and June in 2015. We assessed prevalence of MRSA pneumonia and associated risk factors through logistic regression analysis. Findings: 3702 patients hospitalised with pneumonia were enrolled, with 3193 patients receiving microbiological tests within 24 h of admission, forming the patient population. 1173 (37%) had at least one pathogen isolated (culture-positive population). The overall prevalence of confirmed MRSA pneumonia was 3·0% (n=95), with differing prevalence between continents and countries. Three risk factors were independently associated with MRSA pneumonia: previous MRSA infection or colonisation (odds ratio 6·21, 95% CI 3·25–11·85), recurrent skin infections (2·87, 1·10–7·45), and severe pneumonia disease (2·39, 1·55–3·68). Interpretation: This multicountry study shows low prevalence of MRSA pneumonia and specific MRSA risk factors among community-dwelling patients hospitalised with pneumonia. Funding: None.